MODEL PREFERENSI WORK FROM ANYWHERE PADA GENERASI Z DAN DAMPAKNYA TERHADAP PERILAKU KERJA SERTA STRATEGI MSDM - Injilia Wulan Gratia Wua; Sherly Ernawaty Susanto; Lidya Djuwita Pratiwi Canon (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the Work From Anywhere (WFA) preference model among Generation Z workers in Manado City and its impact on work behavior and Human Resource Management (HRM) strategies. Using a quantitative approach with a survey method, data were collected from 120 respondents who are Generation Z members at public sector institutions including BKN, Bawaslu, and KPU in Manado City, with WFA experience ranging from six months to one year. The research instrument consisted of a Likert-scale questionnaire measuring four constructs: WFA preference, work behavior, HRM strategy, and job satisfaction. Data analysis employed multiple linear regression and Structural Equation Modeling (SEM) using SPSS 26 and AMOS 24. Results indicate that WFA preference significantly and positively influences work behavior (β = 0.462; p < 0.05) and HRM strategies (β = 0.384; p < 0.05). Flexibility and digital connectivity emerged as the dominant dimensions of WFA preference among Generation Z. Moreover, organizations that adopted adaptive HRM strategies reported higher levels of employee engagement and productivity. The study concludes that WFA represents a transformative working model for Generation Z that necessitates structural adjustments in HRM practices, including talent management, performance evaluation, and digital well-being policies. Keywords : Work From Anywhere, Generation Z, Perilaku Kerja, Strategi MSDM, Kepuasan Kerja